SAPI DALAM SOSIAL-BUDAYA MASYARAKAT MADURA ABAD 19-20 - Mohammad Refi Omar Ar Razy; Dade Mahzuni (Siginjai: Jurnal Sejarah, 2022)
This study attempts to analyze the conservation of cattle in Madura and its relationship with social, cultural and economic studies. Cows are very synonymous with the Madura people’s. In the cultural context, the cows has become a custom for the Madura people’s. It is proven by the existence of an event that involves cows in it, namely the Karapan Sapi festival. For the Madura people’s, Karapan Sapi is not only an ordinary festival activity, but in it there are traditional values and also noble values that also involve the dignity of the Madurese. Cows, which are a custom for the Madura people’s, must be taken care of properly. In the social and economic context, the cows symbolizes the structure and class of the Madura people’s and also symbolizes self-esteem in everyday life. Its motto is "etembhang pote mata, angoan apotea tolang" (rather than white of the eye, bone white is better). This means that instead of holding back shame, it is better to maintain self-respect, in Madurese self-esteem also lies in the cows they have. But then cows also become one of the economic tools that apply to the Madura people’s. In this research using historical research consisting of heuristic, criticsm, interpretation and historgiography. In this study we can find out: 1) the pattern of cows conservation in Madura. 2) Cows conservation and its relation to the socio-cultural society of Madura and 3) Cows conservation and its relation to the socio-economic life of the Madura people’s